Ta có: \(2n^2+n-7=2n\left(n-2\right)+5\left(n-2\right)+3\)
\(=\left(2n+5\right)\left(n-2\right)+3\)
Vì \(\left(2n+5\right)\left(n-2\right)⋮\left(n-2\right)\) nên \(3⋮n-2\)
\(\Rightarrow n-2\inƯ\left(3\right)=\left\{\pm1;\pm3\right\}\)
\(\Rightarrow n\in\left\{3;1;5;-1\right\}\)
Vậy \(n\in\left\{\pm1;3;5\right\}\).
2n^2 + n - 7 | n - 2
- 2n^2 - 4n | 2n + 5
5n - 7
- 5n - 10
3
Để ( 2n^2 + n - 7)chia hết cho(n - 2) thì 3 chia hết cho (n - 2)
<=> (n - 2) ∈ Ư(3)
<=> n - 2 = 3 <=> n = 5
hoặc n - 2 = -3 <=> n = -1
hoặc n - 2 = 1 <=> n = 3
hoặc n - 2 = -1 <=> n = 1
Vậy n ∈ {-1;1;3;5} thì 2n^2 + n - 7 chia hết cho n - 2